Sociological issues in the preparation of educational administrators in developing areas with special reference to the Caribbean - Layne, Anthony
This paper examines two fundamental and related issues in the preparation of educational administrators in developing nations, and particularly in the Commonwealth Caribbean, namely, educational administration's relationship to regional development and its relationship to the unequal distribution of power. The first section of the paper questions conventional definitions of development, including the notion that only non-industrialized countries should be classified as "developing." The second section describes regional training programmes for educational administrators that have been carried out in the Caribbean by international organizations. These organizations include the Commonwealth Secretariat, UNESCO's Caribbean Network for Education Innovation for Development, and the United States Agency for International Development (the latter two working in collaboration with each other and The University of the West Indies (UWI)). The third section of the paper discusses the socio-political environment in which educational administrators in the Caribbean have had to operate. It is concluded that these administrators need to recognize clearly that education and politics do mix, and that they must strive to build up their political skills if they are serious about increasing the contribution of education to development
Keywords: Educational administrators